Recent advances in mesenchymal stem cell therapy for multiple sclerosis: clinical applications and challenges - Kamran Sheikhi; Salah Ghaderi; Hassan Firouzi; Sarvenaz Rahimibarghani; Ehsan Shabani; Hamed Afkhami; Hamed Afkhami; Hamed Afkhami; Aref Yarahmadi (Frontiers in Cell and Developmental Biology)
Multiple sclerosis (MS), a chronic autoimmune disorder of the central nervous system (CNS), is characterized by inflammation, demyelination, and neurodegeneration, leading to diverse clinical manifestations such as fatigue, sensory impairment, and cognitive dysfunction. Current pharmacological treatments primarily target immune modulation but fail to arrest disease progression or entirely reverse CNS damage. Mesenchymal stem cell (MSC) therapy offers a promising alternative, leveraging its immunomodulatory, neuroprotective, and regenerative capabilities. This review provides an in-depth analysis of MSC mechanisms of action, including immune system regulation, promotion of remyelination, and neuroregeneration. It examines preclinical studies and clinical trials evaluating the efficacy, safety, and limitations of MSC therapy in various MS phenotypes. Special attention is given to challenges such as delivery routes, dosing regimens, and integrating MSCs with conventional therapies. By highlighting advancements and ongoing challenges, this review underscores the potential of MSCs to revolutionize MS treatment, paving the way for personalized and combinatory therapeutic approaches.